2010
DOI: 10.1098/rspb.2010.1634
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation among non-relatives evolves by state-dependent generalized reciprocity

Abstract: For decades, attempts to understand cooperation between non-kin have generated substantial theoretical and empirical interest in the evolutionary mechanisms of reciprocal altruism. There is growing evidence that the cognitive limitations of animals can hinder direct and indirect reciprocity because the necessary mental capacity is costly. Here, we show that cooperation can evolve by generalized reciprocity (help anyone, if helped by someone) even in large groups, if individuals base their decision to cooperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 38 publications
3
93
0
Order By: Relevance
“…Allowing individuals to differ according to state variables further broadens the possibilities for the evolution of cooperation. State can serve as a signal about the cooperativeness of the social environment [40,43]. This assumes that state is easy to change, like readily mobilizable energy reserves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allowing individuals to differ according to state variables further broadens the possibilities for the evolution of cooperation. State can serve as a signal about the cooperativeness of the social environment [40,43]. This assumes that state is easy to change, like readily mobilizable energy reserves.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, McNamara & Doodson [53] found that the quality of the data on the partner's previous behaviour and hence its state did not influence the outcome of evolution considerably. In games where the evolution of cooperation is influenced by variation in the individuals' own state [40,43], it is reasonable to expect that individuals can accurately estimate their own reserves. As a consequence, one might safely conclude that the accuracy of assessment of inter-individual differences does not seriously affect the results presented here.…”
Section: Resultsmentioning
confidence: 99%
“…males are often damaged in fights, but their interactions are mild compared with the routinely fatal fighting seen in some congeners. Intense inter-male aggression when competing for mating opportunities may turn out to be incompatible with subsequent cooperative behaviour that needs to take place just a few hours later [20,21]. If so, then cooperation may also be absent in the few PFW species with males that fight intensively [11].…”
Section: Discussionmentioning
confidence: 99%
“…Prominent examples include repeated interactions [9], direct reciprocity [10,11], indirect reciprocity [12][13][14], reputation [15], group selection [16], punishment [17][18][19], teaching ability [20,21], aging [22], emotion [23], population growth [24], phenotypic similarity [25]. Recent years have also witnessed a booming interest in structured population [26][27][28][29][30][31], and also a large literature has extended the evolutionary games in complex networks from the regular grids to other real-world networks [32,33], and even mobility of players embedded in networks [34,35].…”
Section: Introductionmentioning
confidence: 99%